2022
DOI: 10.5551/jat.63494
|View full text |Cite
|
Sign up to set email alerts
|

Association between Indoor Temperature in Winter and Serum Cholesterol: A Cross-Sectional Analysis of the Smart Wellness Housing Survey in Japan

Abstract: Issuance of the WHO Housing and health guidelines has paralleled growing interest in the housing environment. Despite accumulating evidence of an association between outdoor temperature and serum cholesterol, indoor temperature has not been well investigated. This study examined the association between indoor temperature and serum cholesterol. Methods:We collected valid health checkup data of 2004 participants (1333 households), measured the indoor temperature for 2 weeks in winter, and divided participants ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…We named this effect "cold debt", with reference to sleep debt [55], which is a state of chronic sleep deprivation leading to physical and mental disorders. In addition to the results presented in this review, the SWH survey revealed that the of residents with high cholesterol was larger in colder homes [56]. A long-term risk of progression of arteriosclerosis is therefore present.…”
Section: The Smart Wellness Housing Cohort Surveymentioning
confidence: 50%
“…We named this effect "cold debt", with reference to sleep debt [55], which is a state of chronic sleep deprivation leading to physical and mental disorders. In addition to the results presented in this review, the SWH survey revealed that the of residents with high cholesterol was larger in colder homes [56]. A long-term risk of progression of arteriosclerosis is therefore present.…”
Section: The Smart Wellness Housing Cohort Surveymentioning
confidence: 50%
“…In addition to people with diabetes mellitus, those with other chronic diseases such as hypertension, cardiovascular diseases, and chronic obstructive pulmonary disease also tend to show exacerbation of their disease condition in the winters [36][37][38] . Hormonal changes, such as the activity of the hypothalamic-pituitary-adrenal axis, serum cortisol levels, and levels of vitamin D are putative factors involved in such aggravation 39,40 . Not only hormonal changes, but even changes in the ambient temperature, humidity, hours of sunshine, eating habits, activity levels, and seasonal events such as Christmas, year end and New Year parties could also lead to worsened glycemic control 20,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is an important risk factor for CVDs. In Umishio et al's research, inadequate indoor temperature (<18 ℃) was positively associated with hyperlipidemia 1) . Unlike outdoor temperature, the indoor temperature is an adjustable factor.…”
Section: See Article Vol 29: 1791-1807mentioning
confidence: 96%
“…In this issue of the Journal of Atherosclerosis and Thrombosis, Umishio et al report the association between indoor temperature in winter and serum cholesterol based upon a cross-sectional analysis of the Smart Wellness Housing Survey in Japan 1) . The indoor temperatures of 2004 participants (1333 households) were measured for 2 weeks in winter, and they were divided into three categories according to average bedroom temperature: 206 warm houses (≥18 ℃), 940 slightly cold houses (12 ℃-18 ℃) and 858 cold houses ( <12 ℃).…”
Section: See Article Vol 29: 1791-1807mentioning
confidence: 99%